2015
DOI: 10.1186/s13048-015-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of mouse ovarian tissue follicle morphology and ultra-structure after vitrifying in biotechnological protocols

Abstract: BackgroundThe aim of the present study was to characterize the morphological and ultrastractural of mouse ovarian tissue with different cryoprotectant solution.ObjectiveAim of this study, is to demonstrae an improved convetional vitrification method on mouse ovarian tissue using different concentrations of ethylene glycol (EG) and/or dimetyl sulfoxide (DMSO) and EG.Materials and methodsMouse ovarian tissue dissected and were randomly assigned to three groups: control, conventional vitrification (CV) and toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
4
8
0
Order By: Relevance
“…The second successful method is the addition of a macromolecule, such as sucrose, in equilibration and vitrification solutions. The addition of sucrose confirmed previous reports that this is more efficient for follicular viability and ultrastructure . Sucrose has high solubility and low viscosity, which could facilitate the exit of water from the cell and decrease the formation of ice crystals; thus, it could protect the cells during the freezing–warming process.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The second successful method is the addition of a macromolecule, such as sucrose, in equilibration and vitrification solutions. The addition of sucrose confirmed previous reports that this is more efficient for follicular viability and ultrastructure . Sucrose has high solubility and low viscosity, which could facilitate the exit of water from the cell and decrease the formation of ice crystals; thus, it could protect the cells during the freezing–warming process.…”
Section: Discussionsupporting
confidence: 84%
“…The first successful method for vitrifying mouse ovarian tissue is addition of EG as permeable agents. Our previous study confirmed that EG in combination with DMSO had the highest protective effects and least ultrastructural damage on the ovarian follicle . Thus, in the present study we used mixed cryoprotectants (EG and DMSO) for ovarian tissue vitrification.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations